ANALISIS LEMBAGA KEUANGAN NON-BANK DAN PERANNYA DALAM PEREKONOMIAN - A Sulaeman; F. I Hudiya; F. R Suhendar; H Khotimah; I. S Mulyani (Jurnal Pendidikan Ekonomi Indonesia, 2020)
This research is motivated by symptoms or phenomena that occur in the Non-Bank Financial Institution sector. There are many types of non-bank financial institutions circulating in the community, including life insurance companies, social insurance companies, pawnshops, pension funds, finance companies, guarantee companies, infrastructure financing companies and Indonesian export financing institutions that have their respective roles and benefits for Public. Non-bank financial institutions have a very important role for the economy. The strategic role of this institution is as a vehicle that is able to collect and channel public funds effectively and efficiently towards improving people's living standards. This study was conducted to find out how the influence of the development of non-bank financial institutions marked by the growth of non-bank financial institution company assets on the progress and growth of the Indonesian economy as measured by gross domestic product (GDP). The method in this study uses a quantitative descriptive method using panel data. The choice of quantitative descriptive in this study was based on research that wanted to examine and see the degree of relationship between the relationship between Non-Bank Financial Institution Assets and the Economic Growth Rate. The object of this research is Economic Growth, namely GDP as the dependent variable and Non-Bank Financial Institution Assets as the independent variable. The data sources in this study were obtained from the Financial Services Authority (OJK) and the Central Bureau of Statistics in 2010-2019.